Baseline of selected essential nutrient elements of an indigenous fruit tree (Mimusops zeyheri) under natural conditions. - Ledwaba, Charlotte Ramasela (My University, 2008)
The mineral nutrition of indigenous crop species is not well documented like other known crop species, thus making it difficult for one to know how to plant and maintain the crops. Mmupudu (Mimusops zeyheri), which, happens to be a wild crop, is one of the indigenous trees of interest to the Discipline of Plant Production, University of Limpopo. The current study gives baseline information that will be important in various environmental physiology studies of this plant. Physiological studies will be necessary to assess the importance of “limiting” mineral nutrients in the accumulation of certain mineral nutrients in Mmupudu in relation to its productivity. The experiment was arranged as a 2 x 3 factorial in RCBD, with the first and second factors being time of sampling and location, respectively. The three locations where data were collected were Chuenespoort, Bochum and Sekgosese. In each location, the experiment was replicated 10 times. Data were analyzed using ANOVA and means were separated using the least significant difference test. The two-factor interaction was nonsignificant (P ≥ 0.10) for both pH and electrical conductivity. Soil pH was not affected by time in all three locations suggesting that abscised flowers and fruitlets have no effect on pH. Leaf K experienced an increase of 65% at Chuenespoort and a decrease of soil K after fruiting by 44%. Leaf and soil P decreased after fruiting in all locations as was the case with Cu. Chuenespoort and Sekgosese experienced a decrease in leaf Mn after fruiting while soil Mn decreased in all locations after fruiting. Sekgosese experienced an increase of 25% soil Mg after fruiting, whereas leaf Mg decreased in all locations.
Thesis (M.Sc. (Agriculture)) --University of Limpopo, 2008
Keywords: Fruit trees; Arboriculture; Mimusops Zeyheri; Indigenous crops; Plant production; Indigenous fruit trees